The Relationship Between Management Skills and Job Satisfaction of Educators at Private Islamic Religious Colleges (PTKIS) in Jambi Province - Hamdi Zas Pendi; Mukhtar Mukhtar; Risnita Risnita (International Journal of Southeast Asia, 2023)
This study was aimed at analyzing the relationship among management skills, leadership style, and interpersonal communication towards job satisfaction of the academic staff of private Islamic higher education either partially or simultaneously. Quantitative research was set up as the method of the research. The design of the research was survey research. The research was carried out at Private Islamic Universities in Jambi Province. The unit of analysis was the academic staff at Private Islamic Universities in Jambi Province. The population was 115 people. The samples were selected by using the total sampling technique. The hypothesis in this study was: management skills, leadership style, and interpersonal communication have a significant relationship either partially or simultaneously on the job satisfaction of academic staff. The hypothesis was tested by using the Pearson Product Moment Correlation technique analysis and multiple regression, with a significance level of 5 percent alpha (? = 0.05). The findings of the research showed that simultaneously, management skills, leadership style, and interpersonal communication have 44.8% relationship on job satisfaction of education.